An overview of fermentation in rice winemaking - Meiwei Koay; Hui Yin Fan; Clemente Michael Vui Ling Wong (jurnal1, 2022)
Rice wine is an alcoholic beverage produced via the fermentation of cereals, primarily rice with starter cultures. It is produced and consumed globally, especially in Asian countries. With the growth of the global rice wine market, the development of high-quality rice wines is gaining increasing interest. This paper reviews and discusses the comprehensive research details of rice wines in different regions, including the selection of starch substrates, comparison of starter cultures’ microbial compositions, compositions of rice wines and its health benefits. The simultaneous saccharification and fermentation (SSF) of rice wine, microorganisms involved in the fermentation, and factors affecting the fermentation process are discussed, thus providing an overview of the rice wine fermentation and the involved study perspectives.